Complete Transcriptome Profiling of Normal and Age-Related Macular Degeneration Eye Tissues Reveals Dysregulation of Anti-Sense Transcription - Kim, Eun Ji (Sci Rep, 2018)
Age-related macular degeneration (AMD) predominantly affects the retina and retinal pigment epithelium in the posterior eye. While there are numerous studies investigating the non-coding transcriptome of retina and RPE, few significant differences between AMD and normal tissues have been reported. Strand specific RNA sequencing of both peripheral retina (PR) and RPE-Choroid-Sclera (PRCS), in both AMD and matched normal controls were generated. The transcriptome analysis reveals a highly significant and consistent impact on anti-sense transcription as well as moderate changes in the regulation of non-coding (sense) RNA. Hundreds of genes that do not express anti-sense transcripts in normal PR and PRCS demonstrate significant anti-sense expression in AMD in all patient samples. Several pathways are highly enriched in the upregulated anti-sense transcripts—in particular the EIF2 signaling pathway. These results call for a deeper exploration into anti-sense and noncoding RNA regulation in AMD and their potential as therapeutic targets.